The otoacoustic emissions-applicability in the diabetic individual: a brief review - Munjal, Manish; Kaur, Hardeep; Munjal, Shubham; Arora, Vineeta; Nanda, Kshitij; Gupta, Pritish; Binepal, Tegbir S.; Patel, Ayame D. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Untoward effects in the organ of corti and the stria vascularis are documented on histopathology in the diabetic individual with consequent hearing impairment. Hearing loss is even hypothesized to be due to the synergistic effect of hyperglycemias plus oxidative stress causing cochlear microangiopathy as well as auditory neuropathy. Control of the glycemic index in the diabetic improves the quality of life (QOL).